Abiotic stress research in crops using -omics approaches: drought stress and banana in the spotlight - Kissel, E.; Vanhove, A.C.; García, S.; Panis, Bartholomeus; Rouard, M.; Cenci, A.; Roux, N.; Zorrilla, J.; Swennen, Rony L.; Carpentier, Sebastien C. (International Society for Horticultural Science, 2016)
Evaluating crop biodiversity is a challenging task and needs to integrate knowledge from different levels. This overview paper offers ways to tackle this challenge, illustrated by the case for drought tolerance in banana. KU Leuven hosts the International Musa Germplasm Collection managed by Bioversity International for safe storage and distribution in order to secure the cropRSQUOs genepool and encourage its use. The latter, however, requires an in-depth knowledge of the variability among the accessions for coping with varying environmental limitations. Our research focuses on variations in drought tolerance by integrating information from different biological levels (genome, transcriptome, metabolome and phenome). Banana originated in the humid tropics, and yields decrease dramatically when the crop is grown in dryer areas. Circumstantial evidence suggests that elements of the Musa balbisiana (B) genome confer greater drought tolerance on banana than those of the Musa acuminata (A) genome. Hence the genomic constitution may affect the stress response. To phenotype different Musa accessions belonging to different genomic groups, we monitored multiple non-destructive and destructive phenotypic plant variables in response to changing water availability. We used multivariate analysis to classify the different variables according to their contribution in explaining the observed variance between accessions. Ultimately, plant phenotype is driven by genes operating to regulate growth combined with environmental limitations. As such, gene and cell function must always be considered in the whole-plant context. Our brief overview of recent applications of -omics approaches in banana research also covers the challenges of applying such -omics approaches to a non-model crop, with a special focus on abiotic stress. As a general workflow, we propose to combine RNA-Seq, proteomics and metabolite analysis to characterize the cellular phenotype and link to the differential genotype. An interdisciplinary network in plant phenotyping should be established to characterize genetic diversity in genebanks and breeding programs.